Knockout of the ABCB1 Gene Increases Susceptibility to Emamectin Benzoate, Beta-Cypermethrin and Chlorantraniliprole in Spodoptera frugiperda - Qi Li; Minghui Jin; Songmiao Yu; Ying Cheng; Yinxue Shan; Peng Wang; Haibin Yuan; Yutao Xiao (Insects, 2022)
ATP-binding cassette transporter B1 (ABCB1, or P-glycoprotein) is known to be an important participant in multidrug resistance in mammals, and it also has been proved as a transporter for some insecticides in several lepidopteran insects, yet the precise function of this transporter in Spodoptera frugiperda is unknown. Here, we generated a SfABCB1 knockout strain of the S. frugiperda using the CRISPR/Cas9 system to explore its potential roles in determining susceptibility to chemical insecticides or Bt toxins. Bioassay results showed that the susceptibility of SfABCB1 knockout strain to beta-cypermethrin, chlorantraniliprole and emamectin benzoate were significantly increased compared with the wild-type strain DH19, whereas there were no changes to Bt toxins for Cry1Ab, Cry1Fa and Vip3Aa. Our results revealed that SfABCB1 plays important roles in the susceptibility of S. frugiperda to beta-cypermethrin, chlorantraniliprole and emamectin benzoate, and imply that overexpression of ABCB1 may contribute to beta-cypermethrin, chlorantraniliprole and emamectin benzoate resistance in S. frugiperda.